Urgensi Public Service Motivation pada Pelayanan e-KTP : Studi Kasus pada Pelayanan e-KTP di Disdukcapil Kabupaten Tangerang - Serin Anggraeni Putri; Udin Syamsudin; Thita Moralitha Mazya (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Public services such as e-KTP are still faced with various problems that have a negative impact on the quality of service for the community. One of the root problems of public service providers is the lack of public service motivation from employees to provide the best service. There are five dimensions of success in public service motivation that play an important role, namely interest in public policy, commitment to the public interest, empathy, self-sacrifice, and belief in justice. These values ​​should be possessed by public employees as public service providers in order to provide the best service to the community. The purpose of this study was to determine the value of Public Service Motivation in e-KTP services at the Tangerang Regency Population and Civil Registry Office using a qualitative approach through observation, interviews, and documentation. The results of the study showed that PSM in e-KTP services at the Tangerang Regency Population and Civil Registry Office was still not optimal, as shown in the results of the following values: 1) Interest in making public policy is low, because employees tend to be passive and lack initiative in being involved in the policy process. 2) Commitment to the public interest is also lacking, reflected in slow service. 3) The nature of compassion is quite good, as seen in the priority of services for those in need at the Tangerang Regency Population and Civil Registry Office. 4) Self-sacrifice is still lacking, with employees reluctant to work extra time. 5) Trust in justice is still not optimal, as seen from complaints about injustice in service.